The Global Social and Economic Consequences of Mountain Cryospheric Change - Rasul, Golam; Molden, David (Frontiers in Environmental Science, 2019)
Mountain cryosphere provides fresh water and other ecosystem services to half of humanity. The loss of mountain cryosphere due to global warming is already evident in many parts of the world, which has direct implications to people living in mountain areas and indirect implication to people living downstream of glaciated river basins. Despite the growing concerns, the relationship between cryosphere change and human society has yet to be assessed systematically. A better understanding of how cryosphere change affects human systems and human security would provide much needed support to the planning of global and regional actions to mitigate impacts and facilitate adaptation. This paper synthesizes the current evidence for and potential impacts of cryosphere change on water, energy, food, and the environment in different mountain regions in the world. The analysis reveals that the changes in the cryosphere and the associated environmental change has already impacted people living in high mountain areas and are likely to introduce new challenges for water, energy, and food security, and exacerbate ecosystem and environmental degradation in the future. The effects of cryospheric changes are also likely to extend to downstream river basins where glacier melt contributes significantly to dry season river flows and supports irrigation, fisheries, and navigation, as well as water supply to many big cities. Appropriate adaptive and mitigative measures are needed to prevent risks and uncertainties being further compounded